THE EFFECT OF THE COMPOSITION OF MICROORGANISMS IN THE ORAL CAVITY ON THE LEVEL OF PROTECTION AGAINST COLONIZATION BY PARODONTAL INFLAMMATORY PROCESSES IN PATIENTS WITH GASTROINTESTINAL DISEASES: AN ANALYSIS OF THE RELATIONSHIP - Shakhnoza Sh. Khodjaeva; Otabek A. Razhabov (Central Asian Journal of Medicine, 2024)
The study conducted at the Department of Dentistry of the Bukhara State Medical Institute in the period from 2020 to 2023 covers the analysis of the relationship between pathologies of the gastrointestinal tract and the characteristics of the oral microbiome.